Treasure Hunt : a novel - Lescroart, John T. (Dutton, 2010)
When the body of Dominic Como, one of San Francisco's most high-profile activists--a charismatic man known as much for his expensive suits as his work on a half dozen nonprofit boards--is discovered, P.I. Mickey Dade and P.I. Wyatt Hunt investigate Como's business associate, Alicia Thorpe--young, gorgeous, and the sister of one of Mickey's friends.